PLAYFULNESS CONTRIBUTING TO MULTIPLE LANGUAGES: PLANNING, DOING AND REVIEWING - Ramos Pereira de Souza, Diego; Alexandre Agreli de Lira Miranda, Ricardo; da Silva Costa, Jucelino; Marcia de Mendonça Oliveira, Girlaine; Aparecida Santos da Silva, Maria; Wilker da Silva, José; de Gouvêa Caldas, Glauco; Maria do Nascimento Domingos, Ramires; Maria Alves, Ivanilda; Bruna da Silva, Maria; de Melo Silva, Inaldevania (Revista Gênero e Interdisciplinaridade, 2025)
Games, toys and games are essential for children’s development, because of their symbolic manifestations and the playful use of different languages: verbal, literary, visual, musical and corporal. This article deals with the rescue of the playful as an educational process, starting with the articulation with the work of multiple languages in the process of systematization following the sequence: PFR (Plan, Do, Reveer) in the interest room, central aspect of the approach HIGH / SCOPE. The case study is aimed at students of Early Childhood Education, aged 3-5 years. This work provided the children with an active learning environment that fostered action / reflection through creative and permanent interactions with people, ideas materials, encouraging children to make choices and make decisions.